A comprehensive evaluation of moisture damage of asphalt concrete mixtures. Issue Volume 18:Issued 2(2017) (1st February 2017) - Sebaaly, Peter E.; Hajj, Elie Y.; Sathanathan, Thileepan; Shivakolunthar, Sivakulan
Abstract: A comprehensive study was conducted to evaluate the impact of liquid and lime additives on the pavement performance of asphalt mixtures from five different sources around the USA. Three types of mixtures were evaluated from each source: untreated, liquid-treated and lime-treated. The measured properties of the 15 mixtures included the dynamic modulus master curves and their resistances to rutting and fatigue at the undamaged and moisture-damaged conditions. The moisture-damaged state consisted of subjecting the mixtures' specimens to six freeze-thaw cycles. First the mixtures from each source were ranked based on their individual properties, i.e. dynamic modulus, permanent deformation and fatigue characteristics. Next, the measured properties of the mixtures were used in a mechanistic analysis to predict the rutting and fatigue lives of flexible pavements constructed with the evaluated mixtures. The estimated rutting and fatigue lives of the flexible pavements were ranked within each source. The analysis of the data showed that ranking of the mixtures within each source based on their individual properties significantly differs from the mixtures based on their rutting and fatigue lives estimated by the mechanistic analysis. This observation led to the conclusion that ranking hot mixed asphalt mixtures solely based on their independent properties provides unreliable recommendations concerning the relative performance of the mixtures. Finally, the performance of the mixtures was compared within each source and showed that lime-treated mixtures out-performed the liquid-treated mixtures for all sources regardless if the source required anti-strip additive or not.